Analysis of emergency braking of a vehicle - Kudarauskas, Nerijus (Transport, 2007)
In this paper, braking of cars is analyzed: the analytic formulas for description of the said process and the diagrams for its illustration are provided, its mode of operation when the wheels of the car are not blocked is discussed upon, the most important factors that impact it are described herein. The key indicators of braking (such as the settled deceleration, the braking distance, etc.) are discussed upon and their values corrected in experimental way are provided. Their graphical responses and numerical values recommended for calculations bound up with technical experts’ examination of traffic accidents as well as more specifically defined methodologies for them are provided.First Published Online: 27 Oct 2010